2015
DOI: 10.1016/j.micinf.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

How bacterial pathogens colonize their hosts and invade deeper tissues

Abstract: Bacterial pathogens have evolved a wide range of strategies to colonize and invade human organs, despite the presence of multiple host defense mechanisms. In this review, we will describe how pathogenic bacteria can adhere and multiply at the surface of host cells, how some bacteria can enter and proliferate inside these cells, and finally how pathogens may cross epithelial or endothelial host barriers and get access to internal tissues, leading to severe diseases in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
424
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 623 publications
(438 citation statements)
references
References 101 publications
7
424
0
7
Order By: Relevance
“…Extracellular interaction. Extracellular components mediate direct, physical contact between a bacterium and its environment, which potentially includes both host cells and other bacteria (15). In S. alvi, as for most Gram-negative bacteria, lipopolysaccharide (LPS) is the major constituent of the outer leaf of the outer membrane, and its synthesis from the carbohydrate products of gluconeogenesis, as well as its export (via the lpt gene products) were essential for cell viability under all conditions (Fig.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular interaction. Extracellular components mediate direct, physical contact between a bacterium and its environment, which potentially includes both host cells and other bacteria (15). In S. alvi, as for most Gram-negative bacteria, lipopolysaccharide (LPS) is the major constituent of the outer leaf of the outer membrane, and its synthesis from the carbohydrate products of gluconeogenesis, as well as its export (via the lpt gene products) were essential for cell viability under all conditions (Fig.…”
Section: Significancementioning
confidence: 99%
“…Adhesion and biofilm formation are often important for host colonization (15). S. alvi grows in a distinct layer adjacent to the gut epithelium, suggesting adherence (12,13) (Fig.…”
Section: Significancementioning
confidence: 99%
“…enteropathogenic E. coli (EPEC), enterotoxigenic E. coli (ETEC), adherent-invasive E. coli (AIEC), diffusely adhering E. coli (DAEC), and Salmonella spp. mediate their pathogenesis via adhesion to and/or invasion of intestinal epithelial cells [2]. The chaperone-usher pathway (CUP) type I pilus adhesin, FimH, mediates adhesion to D-mannosyl residues of CEACAMs, including CEACAM-1, CEACAM-5 and CEACAM-6, and has been associated with EPEC and DAEC infections [78].…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…Multiple studies have shown that efficient binding between bacterial adhesins and host epithelial/endothelial surfaces is a prerequisite for establishing successful colonization [2]. Therefore, the optimal presentation of host receptors for adhesion is critical for bacterial infection and subsequent disease.…”
Section: Introductionmentioning
confidence: 99%
“…Dengan masuk ke dalam sel, patogen dapat menghindari interaksi dengan berbagai molekul sistem imun seperti komplemen, sitokin, dan antibodi serta dapat menghindari ancaman fagositosis oleh fagosit profesional seperti makrofag (Casadevall, 2008;Medzhitov, 2007;Ploegh, 1998). Namun, beberapa hasil penelitian menunjukkan bahwa bakteri dan virus juga dapat masuk ke dalam sel target melalui proses fagositosis (Ribet & Cossart, 2015). Langkah pertama yang dilakukan patogen adalah menginfeksi sel tertentu lalu selanjutnya menginduksi apoptosis pada sel tersebut.…”
Section: Mengapa Patogen Ini Masuk Ke Dalam Sel?unclassified